The Polish State of transplantation - Edyta Medak; Antoni Niedzielski; Karolina Antonik; Andrzej Horoch; Magdalena Brodowicz-Król (Kazimierz Wielki University, 2018)
Organ transplantation is a life-saving people affected, which the body is unwieldy to live. This method involves the implantation, the person get an organ from another man. It is used in the case of end-stage organ failure, among other things, such as the kidneys, heart, liver, lung, pancreas, intestines. This treatment allows you to return to your health about 1-1.5 thousands of people per year. Currently used in transplantation organs mainly come from donors. Only the kidneys and portions of livers can be retrieved from living donors, but the proportion of this kind of downloads is relatively small. It is estimated that in the world which fourteen minutes another person is qualified for surgery, and a daily fifteen people die without being able to look forward to.